2011
DOI: 10.2478/v10012-011-0017-8
|View full text |Cite
|
Sign up to set email alerts
|

Operating and economic conditions of cooling water control for marine steam turbine condensers

Abstract: Operating and economic conditions of cooling water control for marine steam turbine condensers The article presents the operational and economic analysis of controlling the cooling water flow in marine steam turbine power plants. The analysis bases on selected designs of the main condenser cooling water pumps and makes use of the results of investigations performed in inland power plants. Special attention was focused on marine aspects of the operation of those systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Another way to optimize parameters of ship power plants under variable operating conditions, which however interferes also cycle parameters, is application of control of rate of steam turbine condenser. It leads to some savings in amount of energy necessary to drive cooling -water pump and to prevention against condensate overcooling [8].…”
Section: Variable Operational Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to optimize parameters of ship power plants under variable operating conditions, which however interferes also cycle parameters, is application of control of rate of steam turbine condenser. It leads to some savings in amount of energy necessary to drive cooling -water pump and to prevention against condensate overcooling [8].…”
Section: Variable Operational Conditionsmentioning
confidence: 99%
“…The aims can be reached by applying balanced energy conversion which becomes more and more popular both in the case of conventional fuels and alternative ones [2]. As far as sea transport has been concerned this means perfecting the combustion engine power plants and combined systems [3,11,12], improving operational parameters of gas turbines [13] and steam thermal cycles [8], developing novel systems based on fuel cells -SOFC [14] as well as making use of nuclear energy [15]. Special attention should be paid to HTR nuclear reactors.…”
Section: Introductionmentioning
confidence: 99%
“…The hot slag is delivered directly from the combustion chamber (1), after which it is split between two screw coolers (SC-L and SC-R), and then transported to point (6). The mass flow rate of the removed slag is controlled by the rotation speed of the screws.…”
Section: Figmentioning
confidence: 99%
“…the raising of heat exchanger efficiency, the retrofit of hydraulic systems and the improvement or sustenance of their reparability and maintainability. Błaszczyk et al in [6] have found that the overall efficiency of a power plant encompasses the efficiencies of the various power unit components. Among others, they have pointed out that heat loss minimization is the most important factor affecting the loss of power plant efficiency, and there are many areas of potential heat loss in a power plant.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel engine, gas turbine and steam turbine. The contemporary ship power plant is presented in article [14] and operational and economic analysis of some parts of the steam turbine power plant is discussed in article [3]. A summary of losses and energy efficiency of drive motors is presented in paper [18].…”
Section: Introductionmentioning
confidence: 99%